The Dynamics of Bax Channel Formation: Influence of Ionic Strength - Ganesan, Vidyaramanan (The Biophysical Society, 2012)
Mitochondrial outer membrane permeabilization (MOMP) is a complex multistep process. Studies of MOMP in vivo are limited by the stochastic variability of MOMP between cells and rapid completion of IMS protein release within single cells. In vitro models have provided useful insights into MOMP. We have investigated the dynamics of Bax-mediated MOMP in isolated mitochondria using ionic strength as a tool to control the rate of MOMP. We find that Bax can induce both transient permeabilization, detected by protein release, and more substantial long-lasting permeabilization, measured by the rate of oxidation of added cytochrome c. We found that higher ionic strength causes Bax to form small channels quickly but the expansion of these early channels is impeded. This inhibitory effect of ionic strength is independent of tBid. Channels formed under low ionic strength are not destabilized by raising the ionic strength. Increase in ionic strength also increases the ability of Bcl-xL to inhibit Bax-mediated MOMP. Ionic strength does not affect Bax insertion into mitochondria. Thus, ionic strength influences the assembly of Bax molecules already in membrane into channels. Ionic strength can be used as an effective biophysical tool to study Bax-mediated channel formation.